Effect of Solid-state Fermentation on the Nutritional Composition of Nettle (Urtica dioica L.) - Emrah Güngör; Aydın Altop; Guray Erener (Turkish Journal of Agriculture: Food Science and Technology)
The study was aimed to improve the nutritional composition of nettle (Utrica dioica L.) having positive effects on animals by solid-state fermentation. Aspergillus niger was used as a inoculant in fermentation of nettle. Before and after fermentation, crude protein (CP), ash, ether extract (EE), nitrogen-free extract (NFE), crude fiber (CF), hemicellulose (HC), neutral detergent fiber (NDF), acid detergent fiber (ADF) and acid detergent lignin (ADL) contents of nettle were determined. The ash, NFE and HC content of nettle were increased by fermentation. However, A. niger decreased the CF and EE in nettle. The results showed that solid-state fermentation with A. niger can be used to improve the nutritional composition of nettle.